PERBANDINGAN KEJADIAN ISPA PADA BALITA DI DAERAH PERBUKITAN DAN WILAYAH PESISIR KOTA SEMARANG DITINJAU DARI KOMPONEN IKLIMTAHUN 2012 â€“ 2016 - Lestari, Resta; Budiyono, Budiyono; Dewanti, Niki Astorina Yunita (Jurnal Kesehatan Masyarakat (e-Journal), 2018)
Infectious diseases such as ARI caused by viruses and other microoganisms are sensitive to temperature, humidity, and ambient environmental conditions. In Semarang, the temperature and humidity has increased 0.1Â°C and 1.6% respectively during 2011-2015. ARI in children under 5 years had increased during 2012-2015 The study aimed to analyze the differences of ARI occurrence in hilly areas and coastal areas of Semarang City from 2012 to 2016 in terms of climate component. This research is an analytic research with cross sectional approach. Methods of data analysis using Independent T-Test and Mann Whitney with Î± = 5%. Data of ARI occurrence was obtained from monthly report of ARI in child undier five years at primary health care of Mijen and primary health care of Bandarharjo. Data of climate (air temperature, humidity and rainfall) was obtained from Agency for Meteorology, Climatology and Geophysics (BMKG) Semarang. Mean of ARI occurrence in Mijen was 156 cases, air temperature was 26,4 oC, humidity was 76,2% and rainfall was 338,9 mm/month. Mean of ARI in Bandarharjowas 276 cases, air temperature was 28.2 oC, humidity was 76.5% and rainfall was 176.1 mm/month. There are differences of ARI occurrence, air temperature and rainfall in Mijen and Bandarharjo and ARI occurrence based on temperature (<0.01; <0.01; <0.01; <0.01). There is no differences of humidity in Mijen and Bandarharjo, ARI occurrence based on humidity and rainfall (0.585; 0.119; 0.871). This study concluded air temperature has potential impact to ARI.